Improving Students' Understanding of the Hadith through a Contextual Learning Approach in Islamic Education - Harahap, April Parlindungan; Siregar, Marliana; Siregar, Masgahari (Civiliza Publishing, Indonesia., 2025)
Understanding hadith remains a challenge for many students due to traditional teaching methods that emphasize memorization rather than meaningful interpretation, creating a gap between textual knowledge and real-life application. This study aims to explore how the contextual learning approach can enhance students’ comprehension of hadith by connecting prophetic teachings with authentic experiences in Islamic Education classrooms. Using a qualitative research design, data were collected through classroom observations, semi-structured interviews, and document analysis from teachers and students who engaged in contextual learning activities. The findings reveal that contextual strategies such as real-life scenarios, inquiry-based tasks, reflective discussions, and authentic assessments—significantly improved students’ interpretive understanding, motivation, and moral awareness. Students demonstrated the ability to relate hadith messages to everyday situations, while teachers observed deeper engagement and more meaningful learning outcomes. The study concludes that contextual learning offers an effective pedagogical model for strengthening cognitive and affective aspects of hadith comprehension. Its contribution lies in providing empirical evidence that supports shifting Islamic Education from text-centered instruction toward more experience-based, reflective, and student-centered approaches. This research also highlights the need for teacher training to support the implementation of contextual pedagogy and suggests broader application in diverse educational settings.